2003
DOI: 10.1002/eji.200324254
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of Vα14+ natural killer T cells in the innate phase of host protection against Streptococcus pneumoniae infection

Abstract: The present study was designed to elucidate the role of V § 14 + NKT cells in the host defense against pulmonary infection with Streptococcus pneumoniae using J § 281 gene-disrupted mice (J § 281KO mice) that lacked this lymphocyte subset. In these mice, pneumococcal infection was severely exacerbated, as shown by the shorter survival time and marked increase of live bacteria in the lung compared to wild-type (WT) mice. The proportion of V § 14 + NKT cells, detected by an § -galactosylceramide ( § -GalCer)-loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
158
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 52 publications
7
158
0
3
Order By: Relevance
“…43 NKT cells have been shown to secrete proinflammatory cytokines during infections; these mediators are able to stimulate components of the innate and adaptive responses that eliminate the pathogen. [44][45][46][47][48][49][50] In contrast, during other infections, NKT cells have been shown to secrete antiinflammatory cytokines that limit the infection-induced pathology, 51 and we have found elevations in both Th1 and Th2 cytokines in NKT cell-deficient mice following an LCMV infection, suggesting that there is a level of CD1d-dependent control over this response. 41 It is still unknown how or why NKT cells play dual roles during certain infections, with an increase in proinflammatory cytokines controlling a pathogen, whereas in other infections, antiinflammatory cytokines prevent infection-induced tissue damage.…”
Section: Discussionmentioning
confidence: 57%
“…43 NKT cells have been shown to secrete proinflammatory cytokines during infections; these mediators are able to stimulate components of the innate and adaptive responses that eliminate the pathogen. [44][45][46][47][48][49][50] In contrast, during other infections, NKT cells have been shown to secrete antiinflammatory cytokines that limit the infection-induced pathology, 51 and we have found elevations in both Th1 and Th2 cytokines in NKT cell-deficient mice following an LCMV infection, suggesting that there is a level of CD1d-dependent control over this response. 41 It is still unknown how or why NKT cells play dual roles during certain infections, with an increase in proinflammatory cytokines controlling a pathogen, whereas in other infections, antiinflammatory cytokines prevent infection-induced tissue damage.…”
Section: Discussionmentioning
confidence: 57%
“…Absence of CD1d-restricted NKT cells resulted in the reduced recruitment of neutrophils to infected lungs hours after pathogen inoculation [8,9], supporting the view that NKT cells may exert their function by prompt activation and cytokine expression. However, the natural activation, role and effects in vivo of NKT cells during infections is still poorly understood despite the relatively detailed knowledge on NKT cell activation and function in vitro.…”
Section: Introductionmentioning
confidence: 74%
“…CD1d-restricted NKT cells play a role in infections with different types of pathogens including bacteria [2][3][4][5][6][7][8][9]. Several models demonstrate an important contribution by NKT cells to the immune defense and clearance of the pathogen, while NKT cells may also have detrimental effects and cause excessive inflammation or down modulation of a protective immune response.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the C-glycoside induced more of a Th1 (i.e., IFN-␥) response, was longer lasting, and was actually a better adjuvant than the parental compound itself in murine models of malaria and metastatic melanoma (53)(54)(55)(56)(57). Furthermore, ␣-GalCer administration has been shown to be mostly protective activity against viruses (58 -61), bacteria (62)(63)(64)(65)(66)(67), and other pathogens (68,69). In Trypanosoma cruzi, although GPIs and other lipids from this genus can bind to CD1d, those ligands do not stimulate NKT cells (70).…”
Section: ␣-Galactosylceramide (␣-Galcer) and ␣-Galcer Analogsmentioning
confidence: 99%